‘Mind the Gap’: Reconnecting Local Actions and Multi-Level Policies to Bridge the Governance Gap. An Example of Soil Erosion Action from East Africa - Claire Kelly; Maarten Wynants; Linus K. Munishi; Mona Nasseri; Aloyce Patrick; Kelvin M. Mtei; Francis Mkilema; Anna Rabinovich; David Gilvear; Geoff Wilson; William Blake; Patrick A. Ndakidemi (Land, 2020)
Achieving change to address soil erosion has been a global yet elusive goal for decades. Efforts to implement effective solutions have often fallen short due to a lack of sustained, context-appropriate and multi-disciplinary engagement with the problem. Issues include prevalence of short-term funding for ‘quick-fix’ solutions; a lack of nuanced understandings of institutional, socio-economic or cultural drivers of erosion problems; little community engagement in design and testing solutions; and, critically, a lack of traction in integrating locally designed solutions into policy and institutional processes. This paper focusses on the latter issue of local action for policy integration, drawing on experiences from a Tanzanian context to highlight the practical and institutional disjuncts that exist; and the governance challenges that can hamper efforts to address and build resilience to soil erosion. By understanding context-specific governance processes, and joining them with realistic, locally designed actions, positive change has occurred, strengthening local-regional resilience to complex and seemingly intractable soil erosion challenges.